Economic burden of cystic fibrosis care in British Columbia. Issue 2 (4th March 2023) - Desai, Sameer; Zhang, Wei; Sutherland, Jason M.; PhD, Joel Singer; Zhou, Xingzuo; Quon, Bradley S.
Abstract: RATIONALE: Cystic fibrosis (CF) is a progressive multi-organ disease with significant morbidity placing extensive demands on the health care system. No recent estimate of CF health care costs in a Canadian context exists. OBJECTIVES: Provide up-to-date direct cost estimates of the economic burden of CF from the perspective of a Canadian health care system. METHODS: A longitudinal study of retrospective data was completed in British Columbia by linking the Canadian CF Registry with provincial health care administrative databases for the period between 2007 and 2017. MEASUREMENTS: Health care spending (in constant 2017 Canadian dollars) for CF outpatient services, inpatient hospitalizations, medications, and emergency department visits were included. Generalized estimating equations approach for repeated annual cost data over time was used to estimate health care costs. MAIN RESULTS: The overall total direct annual health care spending for CF care in BC increased from 10.6M to 17.2M from 2007 to 2017 (2017, mean costs per CF patient increased from 31.7K to 42.2K; Cost ratio: 1.33, 95%CI: 1.12-1.57). Outpatient medications, inpatient hospitalizations, outpatient services, and emergency department visits were responsible for 56%, 36%, 7.4% and 0.5% of total costs, respectively. CF adults also showed substantial increases in costs over time (Cost ratio from 2017 relative to 2007: 1.61, 95%CI: 1.17-2.22). CONCLUSIONS: The economic burden of CF increased from 2007 to 2017 driven by rising outpatient medication costs primarily in adults with CF. With approximately 75% of the population eligible for highly effectively cystic fibrosis transmembrane conductance regulator (CFTR) modulators, the economic burden of CF is expected to increase at unprecedented rates.